Yield and Quality of Wheat and Soybean in Sole- and Double-Cropping - Caviglia, Octavio Pedro (2011)
In temperate environments, the wheat-soybean [Triticum aestivum L.- Glycine max (L.) Merr.] double-crop system oft en improves the capture and use efficiency of radiation and water in relation to single crops. Here we assessed the yield and quality of wheat and soybean in relay and sequential double-crops as compared with control sole-crops in the southeastern Pampas of Argentina during two seasons (2000/2001-2001/2002). Soybean controls included crops sown on optimum dates or on dates coincident with those of double-crops. Wheat grain yield and protein concentration were similar in both sowing arrangements of relay (skip row, where one wheat row out of four was unsown) and sequential (solid-seeded) double-crops (yield: 4070 vs. 4100 kg grain ha-1; protein: 164 vs. g kg -1). Yields of relay cropped soybean were 74 to 77% of their respective controls sown on the same date. In contrast, yields of sequentially cropped soybean were 85 to 110% of controls sown on the same date. The land equivalent ratio did not differ between cropping strategies and ranged from 1.58 to 1.82. In comparison to sole-crops, double-cropping increased grain yield and glucose equivalent yield by 58 to 82% and harvest residues by 91 to 143%. Late sowing reduced oil concentration of soybean seed in Year 2, when temperature during seed filling accounted for 58% of the variation in oil concentration. Early growing conditions were critical to the yield of double-cropped soybean. Management of the cropping system to increase soybean shoot biomass at first flower (R1) could further enhance the production and environmental benefits of double crops in temperate environments.